Model Quantum Teaching Tipe Tandur Terhadap Keterampilan Kolaborasi Mahasiswa - Dini Maielfi*; Sisri Wahyuni (JIPI (Jurnal IPA dan Pembelajaran IPA), 2020)
One type of 21st-century skills that needs to be developed is collaboration skills. There were many problems found in the observation. They were student collaboration skills that were lacking in the ability to discuss well, agree with each other; carry out roles, responsibilities and work productively in groups; and there needs to be mutual respect in the lecture process. Efforts to apply and familiarize 21st-century skills, especially in collaboration skills, this research uses the Tandur type of quantum teaching-learning model. The purpose of this study was to see the effect of the Tandur type of quantum teaching model on the collaboration skills of STKIP Adzkia students in learning basic science concepts. The type of research used is quasi-experimental research. This research was given different treatment to the two sample classes. This research design is classified as a randomized control group-only design. The results showed that the data were not normally distributed and homogeneous, so the Mann Whitney test was carried out and the probability value was 0.05 with an asymsig value (2 tails) of 0.475, so H0 was accepted. This research concludes that there is no significant effect of the quantum teaching model of the Tandur type on the collaboration skills of STKIP Adzkia students in learning basic science concepts.